IMPLEMENTING CHATBOTS FOR CONSUMER COMPLAINT RESPONSE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Chatbots offer companies potential efficiency gains in consumer complaint handling through real-time automated intake and responses. However, conversational AI also risks frustration, bias, and regulatory non-compliance without adequate human oversight and governance. This legal analysis examines emerging use cases for complaint chatbots. It reviews capabilities like 24/7 availability, process standardization, and multilingual support. However, chatbots struggle to interpret nuance and provide satisfactory resolution alone. A hybrid approach with human agents managing complex disputes likely balances benefits and risks most responsibly. Further empirical research on consumer perceptions and responsible design principles can help guide ethical integration of complaint chatbots.